MARKET BASKET ANALYSIS MENGGUNAKAN ALGORITMA APRIORI BERBASIS BAHASA R (Studi Kasus Transretail Indonesia) - M Jundi Hakim; Yuma Akbar (STIKOM CKI, 2018)
ABSTRACTMarket Basket Analysis are processing technique for discovery of relationships between various kinds of goods. The main Objective of the Market Basket Analysis in retail to provide information for distributors to find out the purchasing behaviour of customers, which can assist distributors in creating the right choice. There are various the algorithm is available to conduct market basket analysis. This journal discusses data mining techniques, with association rules that can help examine customer buying behaviour and held increase sales. The results can provide price references for cross selling, designing promotions and a placing merchandise in stores to increase sales. Keywords: Market Basket analysis; Ritel; Data Mining